Faculty of Medicine, University of Maribor – the students’ perspective / Medicinska fakulteta Univerze v Mariboru – mnenja študentov o študiju - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Are we good? Are we not so good? How are we compared to others? These are the questions we keep asking ourselves. What is it that will make us better and lead us to become the best?